1996
DOI: 10.1111/j.1469-8137.1996.tb04640.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arbuscular mycorrhizal fungi on growth, mineral nutrition and nitrogen fixation of three varieties of common beans (Phaseolus vulgaris)

Abstract: SUMMARYA pot experiment was conducted under glasshouse conditions to investigate the effect of inoculation with four arbuscular mycorrhizal (AM) fungi {Glomus clarum, G. etunicatum, G. manihotis, Gigaspora margarita), either individually or in a mixture, and wdth Rhizobium leguminosarum hiovar phaseoli, on the growth, mineral nutrition, and contribution of biologically fixed Ng, to three nodulating bean {Phaseolus vulgaris) varieties (Carioca, Negro Argel and Rio Tibagi). The ^^N isotope dilution technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…It has been assumed that the significance of the tripartite symbiosis is solely associated with increased P supply to the nodules through the AMF (e.g. Ganry et al 1982;Kawai and Yamamoto 1986;Vejsadová et al 1993;George et al 1995;Ibijbijen et al 1996;Xavier and Germida 2003). However, a number of studies have suggested that signalling mechanisms regulate the early interaction between the three symbionts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that the significance of the tripartite symbiosis is solely associated with increased P supply to the nodules through the AMF (e.g. Ganry et al 1982;Kawai and Yamamoto 1986;Vejsadová et al 1993;George et al 1995;Ibijbijen et al 1996;Xavier and Germida 2003). However, a number of studies have suggested that signalling mechanisms regulate the early interaction between the three symbionts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biotic factors -such as the absence of indigenous rhizobia or arbuscular mycorrhizal fungi (Ibijbijen et al, 1996) -and legume genotype can also affect legume symbiotic dependence. A comprehensive review of this subject was published by Chalk et al (2006).…”
Section: Legume Bnfmentioning
confidence: 99%
“…Variation among cultivars and genotypes in dependence on AM fungi has been found in many crop plants [2,3,[31][32][33][34][35]. Breeding and selection programs often include fertilization regimes that might be expected to select against ability to form mycorrhizae [5,6].…”
Section: Variation In Mycorrhizal Associations Among Cultivarsmentioning
confidence: 99%